Psychoactive Substances and How to Find Them: Electrochemiluminescence as a Strategy for Identification and Differentiation of Drug Species. Issue 16 (24th November 2020) - Brown, Kelly; Allan, Pamela; Francis, Paul S.; Dennany, Lynn
Abstract : The rapid and continued appearance of novel psychoactive substances onto the global drug market continues to highlight the need for the introduction of novel screening methodologies. Here we discuss the potential of electrochemiluminescence (ECL)-based sensors as viable alternatives to address this current gap within forensic practices. By utilizing a variety of luminophores, differences within the mechanisms responsible for luminescence can be exploited providing the potential to identify different drug species that possess similar structural characteristics. Using a combination of iridium-, osmium- and ruthenium-based sensors, a strong proof of concept for not only the utilization of ECL sensors for drug screening but also the development of multi-metal sensing systems has been demonstrated.